Sculpting a Creature with ZBrush and Photoshop. - Bird, Rayce (linkedin.com, 2015)
Bring creatures from the depths of your imagination to life with ZBrush and Photoshop, in these tutorials from concept artist and Face Off champion Rayce Bird.